Adsorption of dyes, herbicides and heavy metals by composites of silica with amino- and sulfo containing polysaccharides - Budnyak, Tatyana; Tertykh, Valentin; Błachnio, Magdalena; Deryło-Marczewska, Anna; Marczewski, Adam (My University, 2016)
Adsorption on polysaccharide derivatives can be a low-cost procedure of choice in water decontamination for extraction and separation of compounds, and a useful tool for protecting the environment. In current study, polysaccharides-silica composites were synthesized by sol-gel method, physical and chemical adsorption of chitosan and carrageenan by silica surface. Obtained adsorbents were applied to adsorption of highly toxic compounds: cationic and anionic dyes, herbicides and heavy metals.
Keywords: chitosan; carrageenan; dyer; herbicides; silica; хітозан; каррагинан; барвник; гербіциди; кремнезем